Comparative effectiveness of laparoscopic versus open colectomy in colon cancer patients: a study protocol for emulating a target trial using cancer registry data - Semaw Ferede Abera; Gabriele Robers; Anika Kästner; Ulrike Stentzel; Kerstin Weitmann; Wolfgang Hoffmann (Journal of Cancer Research and Clinical Oncology)
Abstract Introduction: The objective of this study is to compare the 5 year overall survival of patients with stage I–III colon cancer treated by laparoscopic colectomy versus open colectomy. Methods: Using Mecklenburg-Western Pomerania Cancer Registry data from 2008 to 2018, we will emulate a phase III, multicenter, open-label, two-parallel-arm hypothetical target trial in adult patients with stage I–III colon cancer who received laparoscopic or open colectomy as an elective treatment. An inverse-probability weighted Royston‒Parmar parametric survival model (RPpsm) will be used to estimate the hazard ratio of laparoscopic versus open surgery after confounding factors are balanced between the two treatment arms. Further to the hazard ratio, we will also compute differences in the absolute risk (at 1, 3, and 5 years) and restricted mean survival time (up to 1, 3, and 5 years). A weighted Kaplan‒Meier curve will be used to compare five-year overall survival in both treatment arms. Various comparator and sensitivity analyses will be performed to check the robustness of the results that will be estimated by the RPpsm main model. Treatment period- and stage-specific results will also be provided. Discussion: This study aims to causally model the effect of laparoscopic versus open colectomy on 5 year overall survival using a target trial emulation approach. As the cancer registry data do not cover BMI, comorbidity, and previous abdominal surgery for non-malignant indications, the potential for residual confounding arising from these factors is a limitation of this study. This will be approached in a quantitative bias analysis using the E-method. The results will substantiate existing evidence on the comparative effectiveness of laparoscopic versus open colectomy in patients with stage I–III colon cancer and may guide clinical decisions as to whether a laparoscopic approach is as safe as an open approach in terms of improving 5-year overall survival in these patient groups.